ANALISIS KEBERHASILAN PEMBERDAYAAN DANA ZAKAT PRODUKTIF PADA PROGRAM SEJUTA BERDAYA LAZ AL AZHAR MENGGUNAKAN METODE CIBEST (CENTER OF ISLAMIC BUSINESS AND ECONOMIC STUDIES): STUDI KASUS KSM PENGASINAN DEPOK - Vini Dwi Seswita; Ady Cahyadi (Journal of Islamic Economy and Business (JIsEB), 2023)
This research aims to measure the level of success in empowering mustahik using zakat funds in the One Million Berdaya Program at the Al Azhar Amil Zakat Institution. The success level of zakat empowerment is measured using the CIBEST (Center of Islamic Business and Economic Studies) method. The CIBEST method is a method used to measure the material and spiritual index values of households, in this case the mustahik who are beneficiaries of the One Million Berdaya Program based on the CIBEST Quadrant. The research results showed that the welfare index value of mustahik increased after receiving program benefits by 31.6%. Apart from an increase in the welfare index value, there was a decrease in the material poverty index value after receiving program benefits by 54.5%